Anti-angiogenic Therapy in Cancer: Downsides and New Pivots for Precision Medicine - Lupo, Gabriella; Caporarello, Nunzia; Olivieri, Melania; Cristaldi, Martina; Motta, Carla; Bramanti, Vincenzo; Avola, Roberto; Salmeri, Mario; Nicoletti, Ferdinando; Anfuso, Carmelina D. (Frontiers in Pharmacology, 2017)
Primary solid tumours originate close to pre-existing tissue vasculature, initially growing along such tissue blood vessels, and this phenomenon is important for the metastatic potential which frequently occurs in highly vascularized tissues. Unfortunately, preclinic and clinic anti-antiangiogenic approaches have not been very successful, and multiple factors have been found to contribute to toxicity and tumour resistance. Moreover, tumours can highlight intrinsic or acquired resistances, or show adaptation to the VEGF-targeted therapies. Furthermore, different mechanisms of vascularization, activation of alternative signalling pathways, and increased tumor aggressiveness make this context even more complex. On the other hand, it has to be considered that the transitional restoration of normal, not fenestrated, microvessels allows the drug to reach the tumour and act with the maximum efficiency. However, these effects are time-limited and different, depending on the various types of cancer, and clearly define a specific “normalization window”. So, new horizons in the therapeutic approaches consist on the treatment of the tumour with pro- (instead of anti-) angiogenic therapies, which could strengthen a network of well-structured blood vessels that facilitate the transport of the drug.